Wartości Unii Europejskiej jako wartości konstytucyjne - Cieśliński, Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
One of the greatest challenges of legal orders of modern times is the legal status of values, since there is no doubt that every legal system needs so called moral ground, and axiology is a widely accepted part of legal reasoning. Generally, it is not easy to define what this term means as for lawyers philosophical understanding might be too ambiguous. To cover the most fundamental of values constitutionalism developed a special category named constitutional values, which is currently seen as a well established one. These are not typical norms of behaviors, as they do not evoke rights and obligations and for some they do not even resemble principles as understood by Dworkin and Alexy.There is a common agreement for their high hierarchical position and significance in the system along with the acceptance of the position of a constitutive element of a legal structure, despite the level of generality. The external origin of values might, however, turn out to be problematic, as they are left outside the sphere of discretion of the lawmaker and their content is ready.Still, it is not easy to answer the question of what the category of “constitutional values” means and consists of. Traditionally, there was no doubt that in order to be legally valid values had to be established by the lawmaker, but as the naturalist perspective becomes more and more popular, judicial activism tends to “discover” new values that were not introduced explicitly by legislative actions. What is more, in the liberal democracy one has to face charges of amorality or moral neutrality of law as the result of such values’ choice that might be accepted in modern pluralistic society. There is certainly a common agreement as far as for example freedom, dignity, democracy, equality or rule of law are concerned. But some quest for “real”, traditional morality that is not to be found in the catalogue.
Keywords: Unia Europejska; wartości UE; wartości konstytucyjne